Genotyping and subtyping of Cryptosporidium spp. and Giardia duodenalis isolates from two wild rodent species in Gansu Province, China - Jie Xu; Hua Liu; Yanyan Jiang; Huaiqi Jing; Jianping Cao; Jianhai Yin; Teng Li; Yeting Sun; Yujuan Shen; Xin Wang (Scientific Reports, 2022)
Abstract Cryptosporidium spp. and Giardia duodenalis are commonly detected intestinal protozoa species in humans and animals, contributing to global gastroenteritis spread. The present study examined the prevalence and zoonotic potential of Cryptosporidium spp. and G. duodenalis in Himalayan marmots and Alashan ground squirrels in China's Qinghai-Tibetan Plateau area (QTPA) for the first time. Four hundred ninety-eight intestinal content samples were collected from five counties of QTPA of Gansu province, China. All samples were examined for Cryptosporidium spp. and G. duodenalis by PCR amplification. The resultant data were statistically analyzed by chi-square, Fisher's test and Bonferroni correction using SPSS software 25. 0. Cryptosporidium positive samples were further subtyped through analysis of the 60-kDa glycoprotein (gp60) gene sequence. A total of 11 and 8 samples were positive for Cryptosporidium spp. and G. duodenalis, respectively. Prevalence of Cryptosporidium spp. and G. duodenalis were 2.5% (10/399) and 1.5% (6/399) in Himalayan marmots, 1.0% (1/99) and 2.0% (2/99) in Alashan ground squirrels, respectively. Sequence analysis confirmed the presence of C. rubeyi (n = 2), ground squirrel genotype II (n = 7), chipmunk genotype V (n = 1) and horse genotype (n = 1). The horse genotype was further subtyped as novel subtype VIbA10. G. duodenalis zoonotic assemblages A (n = 1), B (n = 6), E (n = 1) were identified in the present study. This is the first study to identify Cryptosporidium spp. and G. duodenalis in Himalayan marmots and Alashan ground squirrels, suggesting the potential zoonotic transmission of the two pathogens in QTPA.